A mixed slab-ballasted track as a means to improve the behaviour of railway infrastructure. (September 2016) - Gallego, Inmaculada; Sánchez-Cambronero, Santos; Rivas, Ana; Laguna, Ester
The existence of zones along a railway line that have abrupt changes in the vertical track stiffness is a well-known phenomenon. It results in the need for constant maintenance activities to keep the quality of the track within an acceptable range; which, in turn, increases the operational and maintenance costs of the line. The causes of these zones are related to features in the superstructure and infrastructure of the line. This longitudinal variation results in the creation of longitudinal heterogeneity in the value of the vertical track stiffness. To deal with this problem, a new design is proposed in this paper that is focused on different infrastructure components. A three-dimensional finite element model of a section of railway track is developed in order to analyse the behaviour of both superstructure and infrastructure in response to the passage of railway loads. The proposed model, and hence the new design, is applied to a real Spanish high-speed rail line that is being constructed between Lemoa and Galdakao in the Basque Country. This line goes through an area with a complex topography and it is projected that about 70% of its length will occur in tunnels or on bridges. This characteristic is used to show the advantages and applicability of the proposed cross-section design to achieve a better homogeneity in the value of the vertical track stiffness and, therefore, to reduce the consequences (from a technical and economic point of view) of this variation on the operation of the line.